Unique nasal turbinal morphology reveals Homunculus patagonicus functionally converged on modern platyrrhine olfactory sensitivity. Issue 167 (June 2022) - Lundeen, Ingrid K.; Kay, Richard F.
Abstract: The phyletic position of early Miocene platyrrhine Homunculus patagonicus is currently a matter of debate. Some regard it to be an early member of the Pitheciidae, represented today by the sakis, uakaris, and titi monkeys. Others view Homunculus as a stem platyrrhine, part of a group that diversified in Patagonia and converged in some respects on modern pitheciine dental and gnathic morphology and perhaps seed-eating specialization. New details of its internal nasal anatomy are pertinent to resolving this debate. In addition, they provide a new perspective on how modern platyrrhine olfactory sensitivity evolved. Here we reconstruct the internal nasal anatomy of Homunculus from high-resolution computed tomography scans. This species has three ethmoturbinals, the scrolls of bone in the nasal fossa that were covered in sensory epithelium in vivo. This condition stands in stark contrast to extant platyrrhines, and indeed to all other haplorhines, which have only two ethmoturbinals or, in the case of all pitheciid platyrrhines, only one ethmoturbinal. Quantitatively, however, Homunculus has an olfactory turbinal surface area that falls within the modern platyrrhine distribution, suggesting that while turbinal numbers differ, olfactory sensitivity in this taxon was likely comparable to that of modern platyrrhines. These new data from the fossil record provide further support for the hypothesis that Homunculus is a stem platyrrhine that functionally converged on modern platyrrhines rather than being an early representative of any extant clade.